An Evaluation of VAS Reanastomosis Done by Microsurgery - Singh, Arun Kumar; Tahiliani, N. D. (Indian Journal of Plastic Surgery, 1983)
A controlled experimental study of microsurgical vas reanastomosis has been done and compared with the conventional method. The superiority of microsurgical methods has been demonstrated, even though the procedure is more time consuming.